Key competences in VET : Germany - Hensen-Reifgens, Kristina Alice [Verfasser] (My University, 2015)
"Education, training and competencies are significant influencing factors in terms of both the economic growth of a country as well as productivity and innovation. However, education and training is also a prerequisite for the participation by each individual in society and for their integration within the labour market. The risk of unemployment is also reduced by the acquisition of competences, a factor which goes hand in hand with education and training. In recent years, the concept of competence has become a central idea in the different areas of the education and training system. The quality of education and training processes is no longer defined exclusively by standards focussed on inputs, such as teaching staff qualifications or the facilities offered by the training and teaching providers. Instead, the focus has increasingly been on the actual learning outcomes achieved by pupils, apprentices and students. Nevertheless, for companies, relevant factors in the development of competences include the relevance of work tasks to learning, the scope available to trainees when performing their tasks, the specialist competence of the trainers and the social integration of apprentices. In recent years, the concept of competence has become a central idea in the different areas of the education and training system. The quality of education and training processes is no longer defined exclusively by standards focussed on inputs, such as teaching staff qualifications or the facilities offered by the training and teaching providers. Instead, the focus has increasingly been on the actual learning outcomes achieved by pupils, apprentices and students. Nevertheless, for companies, relevant factors in the development of competences include the relevance of work tasks to learning, the scope available to trainees when performing their tasks, the specialist competence of the trainers and the social integration of apprentices." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.5 Standards in der beruflichen Bildung; L 1.1.2 Handlungs- und Lernfeldorientierung; S 2.2.2.1 Ausbildungsordnungen; Berufsausbildung; Schlüsselqualifikation; Handlungskompetenz; Kompetenzorientierung; Ausbildungsordnung; Industriekaufmann